Staphylococcal scalded skin syndrome pada bayi: laporan kasus - Alberto Afrian; Florencia Christina Sindhu; Peter Prayogo Hsieh; Felicia Emiliana Hosea; Anak Agung Made Sucipta; Tjokorda Dalem Pemayun (Intisari Sains Medis, 2022)
Background: Under-five populations are at higher risk of Staphylococcal Scalded Skin Syndrome (SSSS). The incidence of SSSS in developing countries is still a concern because the staphylococcal infection rate is high. This report aims to describe the clinical profiles of SSSS in infants below 1-year-old. Case: 7 month-old baby boy came with a chief complaint of skin blister for 7 days. It had been preceded by erythema on the right axilla, which turned into blisters on both axilla, perioral, trunk region, and both extremities the following day. The complaint was accompanied by fever. Five days before, he had experienced the common cold. On examinations, he was alert, weighed 9.1 kg, with a heart rate of 134 beats/minute, respiratory rate 40 times/minute, SpO2 98%, and axillary temperature 37.8oC. There were crusts and blisters on the face and trunk with positive Nikolsky’s sign. Genital and lower extremities looked erythematous. Laboratory results showed leukocytes 19,240/uL, neutrophil 50.7%, lymphocytes 35.2%, hemoglobin 9.9 g/dL, hematocrit 30.2%, and platelet 679,000 /uL. He was diagnosed with SSSS and was suggested for hospitalization. He received maintenance fluid therapy with D5%:¼NS 100 ml/kg/day, Cefotaxime injection 3 x 35 mg/kg, Paracetamol syrup 3 x 10 mg/kg, Fusidic Acid 2% cream twice a day, Gentamicin eye ointment 0.3% twice a day, and non-adherent dressing twice a day. He was discharged in good condition after 5 days of hospitalization. Conclusion: The knowledge about the clinical profiles of SSSS is important in order to give rapid management and reduce mortality.   Latar Belakang: Populasi di bawah usia 5 tahun rentan mengalami Staphylococcal scalded skin syndrome (SSSS). Di negara-negara berkembang, insidens SSSS masih tinggi karena infeksi staphylococcus masih banyak terjadi. Laporan kasus ini ditulis untuk memberi gambaran mengenai SSSS pada bayi berusia di bawah 1 tahun. Kasus:  Bayi laki-laki berusia 7 bulan dibawa dengan keluhan utama kulit melepuh sejak 7 hari sebelumnya. Keluhan didahului kemerahan di ketiak kanan dan keesokan harinya, kulit di ketiak kanan, kiri, dan daerah sekitar bibir, dada, perut, kemaluan, serta kedua tungkai melepuh. Dua hari kemudian, kulit di seluruh tubuh mengelupas. Keluhan disertai dengan demam. Lima hari sebelumnya, pasien mengalami pilek. Pada pemeriksaan, pasien sadar dengan berat badan 9,1 kg, denyut nadi 134 kali/menit, laju pernafasan 40 kali/menit, SpO2 98%, dan suhu aksila 37,8oC. Kulit tampak melepuh disertai krusta pada wajah, dada, abdomen,dan punggung. Tanda Nikolsky positif. Daerah ekstremitas bawah dan genital tampak kemerahan. Pemeriksaan darah menunjukkan leukosit 19.240/uL, neutrofil 50,7%, limfosit 35,2%, hemoglobin 9,9 g/dL, hematokrit 30,2%, dan trombosit 679.000 /uL. Dokter mendiagnosis pasien mengalami SSSS dan menyarankan rawat inap. Pasien menerima terapi cairan rumatan dengan D5%:¼NS 100 ml/kg/hari, Cefotaxime injeksi 3 x 35 mg/kg, Parasetamol sirup 3 x 10 mg/kg, krim Asam Fusidat 2% 2 kali/hari, salep mata Gentamisin 0,3% 2 kali/hari, dan perawatan luka 2 kali/hari. Setelah dirawat selama 5 hari, pasien sembuh dan diizinkan pulang. Simpulan: Pengetahuan mengenai gambaran klinis SSSS penting untuk memberi tatalaksana yang cepat dan tepat sehingga mortalitas dapat ditekan.